Skew lattices - Srinivas,K. V. R (Universidad Católica del Norte, Departamento de Matemáticas, 2011)
In this paper mainly important properties of skew lattices and symmetric Lattices is obtained. A necessary and sufficient condition for skew lattice to be symmetric is obtained. Maximal element of a skew lattice is also obtained.